Clinical effects of early sacubitril/valsartan administration in patients with ST-segment elevation myocardial infarction: a systematic review and meta-analysis. (14th October 2021) - Condello, F; Cannata, F; Sturla, M; Pini, D; Ferrante, G; Condorelli, G; Stefanini, G G
Abstract: Introduction: The combination of sacubitril, a neprilysin inhibitor and valsartan, an angiotensin receptor blocker, has been proven to be a game-changer in reducing morbidity and mortality in patients with chronic heart failure with reduced ejection fraction. Recent evidence regarding the early use of sacubutril/valsartan in patients after ST-segment Elevation Myocardial Infarction (STEMI) are emerging. Purpose: To provide a comprehensive synthesis of effect estimates, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs) directly comparing sacubitril/valsartan and an ACE-inhibitor early after successful primary percutaneous coronary intervention (pPCI) in patients presenting with STEMI Methods: We searched the PubMed, EMBASE and Cochrane databases from inception to March 28, 2021 to identify RCTs that report clinical outcomes and compare sacubitril/valsartan versus an ACE-inhibitor in patients presenting with STEMI after pPCI. The primary efficacy endpoint was the risk of hospitalization for heart failure. Secondary efficacy endpoints were major adverse cardiac events (MACE) and left ventricle ejection fraction (LVEF). Safety endpoints were hypotension, hyperkalemia, worsening renal function and angioedema. Pooled risk ratios (RR) and mean differences (MD) with 95% confidence intervals (CIs) were used as summary statistics for endpoints of interest and were calculated using a random-effects model according to DerSimonian and Laird. Results: A total of three studies with 493 patients randomly allocated to sacubitril/valsartan (n=247) or ACE-inhibitor (n=246) were included for analysis. Main study and patient characteristics are reported in figure1. Heterogeneity between studies was low. Individual trial definitions of MACE and adverse events were used in the analysis (figure 1). Sacubitril/valsartan was associated with a significant reduction in the risk of heart failure hospitalizations (RR, 0.55; 95% CI 0.39–0.79, P<0.01, event rate 15.4% vs 28.5%, number needed to treat 8), MACE (RR, 0.64; 95% CI, 0.48–0.84, P<0.01, event rate 20.2% vs 33.3%, number needed to treat 8), and with a significant improvement of LVEF (MD, 3.09; 95% CI, 1.70–4.49, P<0.01), (figure 2). No significant difference was found between sacubitril/valsartan and ACE-inhibitors regarding the incidence of hypotension (RR, 1.42; 95% CI, 0.74–2.72, P=0.29), hyperkalemia (RR, 0.44; 95% CI 0.06–3.08, P=0.41) and worsening renal function (RR, 0.70; 95% CI 0.22–2.24, P=0.55), (figure2). No angioedema was observed in included studies. Conclusion: This is the first systematic review and meta-analysis comparing sacubitril/valsartan and ACE inhibitors in STEMI patients. Based on the presented findings and larger data on the horizon, we may soon find sacubitril/valsartan to be an important addition to our arsenal in improving care to STEMI patients. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Italian Ministry of Education